Development of a modified co-precipitation route for thermally resistant, high surface area ceria-zirconia based solid solutions - PAPPACENA, ALFONSINA (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2010)
In this work a modified co-precipitation route for ceria-zirconia based material with a high surface area, high thermal stability and enhanced OSC properties has been developed and the importance of the addition of surfactants and H2O2 in order to promote the stability of these materials at high temperatures has been developed.